INDONESIAN FOREIGN RELATIONS WITH SAUDI ARABIA DURING THE JOKO WIDODO GOVERNMENT (Journal of Pharmaceutical Negative Results, 2022)
Indonesia under the leadership of President Joko Widodo began to strengthen diplomatic relations with Saudi Arabia. One year after being sworn in as President of Indonesia, Joko Widodo made a state visit to Saudi Arabia on September 11, 2015. The main objective of the visit was to strengthen the cooperation relationship between Indonesia and Saudi Arabia, which had experienced passivity since King Faisal Ibn Abdul Aziz Al-Saud's first visit to Indonesia on June 10, 1970, by utilizing the potential and resources of both countries for the welfare of the people of both countries. Based on this, this study was conducted to describe and analyze Indonesia's foreign relations with Saudi Arabia during the Joko Widodo administration, starting with the foreign relations policy of the Joko Widodo administration which looked more aggressive in establishing bilateral relations with the Saudi government. Arabia. This research was conducted qualitatively where the data sources were obtained from observations, interviews, documentation, and visual materials. In determining the informants, selected purposively to get in-depth information from one informant and scroll to other informants. Meanwhile, researchers conducted literature studies and other document searches to collect supporting data and evaluated using data reduction methods. Research shows that the application of Indonesia's foreign relations to Saudi Arabia during the reign of Joko Widodo has resulted in 11 collaborations as outlined in a Memorandum of Understanding (MoU) covering the fields of economy, politics, and culture. The MoU is the initial stage in efforts to increase trade cooperation between the two countries and can encourage economic growth by increasing the value of Indonesia's investment and exports to Middle Eastern countries, especially Saudi Arabia. In the MoU agreed by the two countries (the Republic of Indonesia and Saudi Arabia) it is also clear that most points of cooperation are found in trade relations. Therefore, the government of the Republic of Indonesia needs to evaluate the field/sector of cooperation, it is recommended to expand and further detail the sector of cooperation in other fields such as the field of law, defense and security, and other fields.]